Inelastic deformation and failure of tungsten carbide under ballistic-loading conditions - Hazell, Paul J.; Appleby-Thomas, Gareth J.; Herlaar, K.; Painter, Jonathan (Elsevier, 2010)
High-speed photography has been used to investigate the dynamic behaviour of similar grades of WC-Co hardmetals during ballistic impacts with velocities in the range of 28-484 m/s. Key features of the failure of similar grades of WC-Co materials during complimentary impacts have been observed and discussed. In particular, fast moving fragments were observed to emanate from the point of impact and flow radially across the target's surface analogous to the processes of interface defeat. Further, as the velocity of impact was increased a non-linear increase in the indentation depth was observed that corresponded with an apparent onset of trans-granular fracture in the WC crystallites. Comparisons with ANSYS AUTODYN™ simulations were made and good correlation has been established between the measured inelastic deformation and computations using a simple strain-hardening model.
Keywords: shock; impact; tungsten carbide; armour-piercing bullets; computational modelling.